The Venus Emissivity Mapper Emulator 2.0: a NIR camera system for Venus analogue field measurements - Garland, Stephen Patrick; Adeli, Solmaz; Müller, Nils; Althaus, Christian; Dyar, M. D.; Smrekar, S.; Nunes, Daniel C.; Domac, Akin; Alemanno, Giulia; Barraud, Oceane; Maturilli, Alessandro; Hamilton, Christopher W.; et al. (Infrared Remote Sensing and Instrumentation XXXII, 2024)
Both NASA’s VERITAS and ESA’s EnVision missions to Venus incorporate a Venus Emissivity Mapper (VEM) to characterize the surface and distinguish basalt from more felsic rock types. Though Venus’ optically dense atmosphere makes direct observations of the surface challenging, five windows in the CO2 spectrum near 1 micrometer will be exploited by the VEM instrument. In preparation for these missions, an analog of the VEM instrument (VEMulator2.0) was constructed for field measurements. It was used in a two-week field campaign at Venus-analog sites in Iceland in August 2023 as part of a VERITAS field campaign to collect multi-frequency reflectance measurements of volcanic rocks of varying age and surface conditions, as well as to measure emission from recently erupted lava with hot spots up to ~400°C. The goal of the work was to train scientists and to help assess the capability of the VEM instrument to detect differences in surface composition in a wide variety of volcanic rocks in the field with the limited spectral information provided by six bands. In addition, samples of the imaged regions were collected to be analyzed in detail at the Planetary Spectroscopy Laboratory at DLR in Berlin. Comparing field and laboratory spectra gives insights into the efficacy and limitations of the analog instrument. This paper describes the emulator design and calibration procedure as well as first results from field and laboratory measurements.